Elevated Excitatory Input to the Nucleus Accumbens in Schizophrenia: A Postmortem Ultrastructural Study - McCollum, Lesley A.; Walker, Courtney K.; Roche, Joy K.; Roberts, Rosalinda C. (Schizophrenia bulletin, 2015)
The cause of schizophrenia (SZ) is unknown and no single region of the brain can be pinpointed as an area of primary pathology. Rather, SZ results from dysfunction of multiple neurotransmitter systems and miswiring between brain regions. It is necessary to elucidate how communication between regions is disrupted to advance our understanding of SZ pathology. The nucleus accumbens (NAcc) is a prime region of interest, where inputs from numerous brain areas altered in SZ are integrated. Aberrant signaling in the NAcc is hypothesized to cause symptoms of SZ, but it is unknown if these abnormalities are actually present. Electron microscopy was used to study the morphology of synaptic connections in SZ. The NAcc core and shell of 6 SZ subjects and 8 matched controls were compared in this pilot study. SZ subjects had a 19% increase in the density of asymmetric axospinous synapses (characteristic of excitatory inputs) in the core, but not the shell. Both groups had similar densities of symmetric synapses (characteristic of inhibitory inputs). The postsynaptic densities of asymmetric synapses had 22% smaller areas in the core, but not the shell. These results indicate that the core receives increased excitatory input in SZ, potentially leading to dysfunctional dopamine neurotransmission and cortico-striatal-thalamic stimulus processing. The reduced postsynaptic density size of asymmetric synapses suggests impaired signaling at these synapses. These findings enhance our understanding of the role the NAcc might play in SZ and the interaction of glutamatergic and dopaminergic abnormalities in SZ.